Genome-Wide Patterns of Differentiation Among House Mouse Subspecies. Issue 1 (3rd July 2014) - Phifer-Rixey, Megan; Bomhoff, Matthew; Nachman, Michael W
Abstract: One approach to understanding the genetic basis of speciation is to scan the genomes of recently diverged taxa to identify highly differentiated regions. The house mouse, Mus musculus, provides a useful system for the study of speciation. Three subspecies ( M. m. castaneus, M. m. domesticus, and M. m. musculus ) diverged ∼350 KYA, are distributed parapatrically, show varying degrees of reproductive isolation in laboratory crosses, and hybridize in nature. We sequenced the testes transcriptomes of multiple wild-derived inbred lines from each subspecies to identify highly differentiated regions of the genome, to identify genes showing high expression divergence, and to compare patterns of differentiation among subspecies that have different demographic histories and exhibit different levels of reproductive isolation. Using a sliding-window approach, we found many genomic regions with high levels of sequence differentiation in each of the pairwise comparisons among subspecies. In all comparisons, the X chromosome was more highly differentiated than the autosomes. Sequence differentiation and expression divergence were greater in the M. m. domesticus – M. m. musculus comparison than in either pairwise comparison with M. m. castaneus, which is consistent with laboratory crosses that show the greatest reproductive isolation between M. m. domesticus and M. m. musculus . Coalescent simulations suggest that differences in estimates of effective population size can account for many of the observed patterns. However, there was an excess of highly differentiated regions relative to simulated distributions under a wide range of demographic scenarios. Overlap of some highly differentiated regions with previous results from QTL mapping and hybrid zone studies points to promising candidate regions for reproductive isolation.